Penerapan Metode Simple Additive Weighting (SAW) Dalam Pemilihan Peminatan Jurusan Siswa di SMK Mandalahayu - Satria Satria .; Rinanti .; Kikim Mukiman; Zaenal Mutaqin Subekti (Jurnal ICT : Information Communication & Technology, 2021)
SMK Mandalahayu Bekasi is one of the schools in the city of Bekasi which routinely carries out the selection of majors for its students every year. The major is intended so that later students can complete school according to their interests and abilities before continuing to a higher level. The current majors selection process has drawbacks, including it takes a long time and the results obtained are less accurate because there could be many mistakes due to the unavailability of a special application to support these calculations. In addition, the element of subjectivity is quite high because the criteria used are still few and less relevant. To overcome this problem, a decision support system is made to determine the selection of majors. In this study using the Simple Additive Weighting (SAW) method. The criteria used are Mathematics SKHUN scores, Indonesian SKHUN scores, English SKHUN scores, Written Test scores and Interview Test scores. The final result of this study found that the decision support system with the SAW method was able to overcome problems in the selection process of majors at SMK Mandalahayu Bekasi. From taking a sample of several students who have been calculated using the SAW method, the correct major is AP because the value is 79, RPL because the score is between 90-100 and AK, because the score is between 80-89